Об одной проблеме минимума со свободной границей - Шевченко, А.И.; Миненко, А.С. (Видавничий дім "Академперіодика" НАН України, 2007)
Solvability of a boundary-value problem with the Bernoulli condition on a free boundary is proved. By using the Ritz method, an approximate solution convergent to the exact solution in the metric C is constructed.